Comparative evaluation of nebulised 3% saline versus nebulised 0.9% saline in the treatment of acute bronchiolitis - A., Pragalatha Kumar; Rajarathinam, Indhuja; Gowdra, Aruna (International Journal of Contemporary Pediatrics, 2019)
Background: Acute bronchiolitis is the most common respiratory tract infection in young children. Despite the high prevalence of acute bronchiolitis, no consensus exists on the management. Studies have shown that except oxygen therapy, no other treatment found to be effective. Hence, the present study was conducted to find out the efficacy of nebulised 3% saline versus is 0.9% saline for the treatment of acute bronchiolitis. Methods: A prospective randomized controlled study of 150 children between the age group of 2 months to 24 months with signs and symptoms of Acute Bronchiolitis admitted to Indira Gandhi Institute of Child Health, Bangalore from January 2016 to December 2016 formed the study group, they were randomized into 2 groups, one received 3% saline nebulization and the other received 0.9% saline. Results: A total of 150 children were enrolled in the study, 75 children (group A) received 0.9% saline and 75 children (group B) received 3% saline. At 24 hours, the mean clinical severity score for group A was 2.49±1.03 and group B was 2.16±0.49 (P=0.013). The duration of hospital stay was shorter (1-3 days) in 3% saline with a mean of 2.35 days and was longer (3-5 days) in 0.9% saline with mean value of 4.04 days which was statistically significant (p <0.001). Conclusions: 3% saline nebulization can be used as an effective treatment for acute bronchiolitis. It significantly reduced the clinical severity score and length of hospital stay compared to 0.9% normal saline.